Severe Quantitative Scale of Acanthosis Nigricans in Neck is Associated with Abdominal Obesity, HOMA-IR, and Hyperlipidemia in Obese Children from Mexico City: A Cross-Sectional Study - Ana I. Burguete-García; Alan Gilberto Ramírez Valverde; Meztli Espinoza-León; Isaac Sánchez Vázquez; Evelyn Yazmín Estrada Ramírez; Itzel Maldonado-López; Alfredo Lagunas Martínez; Cinthya Estefhany Diaz Benítez; Roberto Karam Araujo; Diana Fernández-Madinaveitia; Adriana E. Anides Fonseca; Miguel Cruz; et al. (Hindawi Limited, 2022)
Background. Acanthosis nigricans (AN) is a clinical sign that commonly occurs in obesity; however, its specificity and sensitivity have been controversial. It is unknown if AN severity degree can be a useful marker for cardiometabolic disorders screening. We suggest that the stratified analysis of AN severity degree in neck by Burke's scale could be a useful tool in the screening of cardiometabolic alterations in obese children. Objective. The aim of this study was the association of AN severity degree in neck by Burke's scale with anthropometric, biochemical, and inflammatory parameters in obese school-age children from Mexico City. Methods. A cross-sectional study was conducted, including 95 obese school-age children stratified by AN severity degree in neck by Burke's scale. Anthropometric and fasting biochemical measurements were determined. Variables were compared by x2 test for frequencies and one-way ANOVA with Bonferroni posttest for continuous variables. Linear regression analysis adjusted by gender, BMI, and age was performed to evaluate the association between AN severity degree and cardiometabolic alterations. Statistical significance was set at p<0.05. Results. As AN severity degree in neck by Burke's scale increased, diastolic blood pressure (p=0.001) and triglycerides (p=0.02) significantly increased and adiponectin significantly decreased (p=0.02). Positive associations between grade 3 AN and waist circumference, HOMA-IR, triglycerides, total cholesterol, and LDL cholesterol were observed. Conclusion. Our findings could be used to identify an easier clinical tool to prevent obesity progression and its complications in pediatrics. There are no similar studies.